Inequality and happiness: when perceived social mobility and economic reality do not match - Bjørnskov, Christian; Dreher, Axel; Fischer, Justina A. V.; Schnellenbach, Jan; Gehring, Kai (Freiburger Diskussionspapiere zur Ordnungsökonomik, 2013)
We argue that perceived fairness of the income generation process affects the association between income inequality and subjective well-being, and that there are systematic differences in this regard between countries that are characterized by a high or, respectively, low level of actual fairness. Using a simple model of individual labor market participation under uncertainty, we predict that high levels of perceived fairness cause higher levels of individual welfare, and lower support for income redistribution. Income inequality is predicted to have a more favorable impact on subjective well-being for individuals with high fairness perceptions. This relationship is predicted to be stronger in societies that are characterized by low actual fairness. Using data on subjective well-being and a broad set of fairness measures from a pseudo micro-panel from the WVS over the 1990-2008 period, we find strong support for the negative (positive) association between fairness perceptions and the demand for more equal incomes (subjective well-being). We also find strong empirical support for the predicted differences in individual tolerance for income inequality, and the predicted influence of actual fairness. -- Happiness ; life satisfaction ; subjective well-being ; inequality ; income distribution ; redistribution ; political ideology ; justice ; fairness ; World Values Survey